Drying Properties and Quality Parameters of Dill Dried with Intermittent and Continuous Microwave-convective Air Treatments - Okan Eştürk (Journal of Agricultural Sciences, 2010)
In this study, influence of various microwave-convective air drying applications on drying kinetics, color and sensory quality of dill leaves (Anethum graveolens L.) were investigated. In general, increasing the drying air temperature decreased the drying time, and increased the drying rate. Increasing microwave pulse ratio increased the drying time. Page, Logarithmic, Midilli et al, Wang & Singh and Logistic models were fitted to drying data and the Page model was found to satisfactorily describe the microwave-convective air drying curves of dill leaves. Comparing to the fresh dill, lightness (L*), greenness (-a*) and yellowness (+b*) decreased for all drying applications. The deviation from fresh product color (∆E*) increased as pulse ratio increased and drying air temperature decreased. Considering the product quality, continuous microwave-convective air drying combinations gave better results than intermittent microwave-convective air drying in terms of color and sensory evaluation results.